Web-age information management : 17th International Conference, WAIM 2016, Nanchang, China, June 3-5, 2016, Proceedings.: 17th International Conference, WAIM 2016, Nanchang, China, June 3-5, 2016, Proceedings. Part I (2016) - Unknown
No abstract available